Medieval art, architecture and archaeology at Rochester
1 online resource
Keywords: This collection of papers, first delivered at the BAA's annual conference in 2002, celebrates medieval Rochester, including both cathedral and castle, an outstanding pair of surviving monuments to the power of contemporary church and state. The contributions demonstrate the great interest of these understudied buildings, their furnishings, and historical and archaeological contexts: from the rich documentary evidence for the Anglo-Saxon town to the substantial surviving fabric of the 11th, 12th and 13th centuries. Shrines, monuments, woodwork and seals are all fully covered, as well as the medieval monks themselves. There is also a piece on Archbishop Courtenay's foundation of the nearby collegiate church at Maidstone, Kent.